2009
DOI: 10.1002/pds.1722
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between thiazolidinedione use and cardiovascular outcomes and all‐cause mortality among patients with diabetes: a time‐updated propensity analysis

Abstract: Purpose To investigate the association of the thiazolidinediones (TZDs), rosiglitazone and pioglitazone, together and individually on the risk of cardiovascular outcomes and all-cause mortality, using time-updated propensity score adjusted analysis Methods We conducted a retrospective cohort study in a large vertically integrated health system in southeast Michigan. Cohort inclusion criteria included adult patients with diabetes treated with oral medications and followed longitudinally within the health syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…Our findings are similar to a recent retrospective study by Habib et al, 29 which found no difference in AMI between TZDs; however, they contrast another retrospective analysis of a younger, healthier insured population receiving rosiglitazone or pioglitazone by Gerritus et al 15 In review of administrative claims from US health plans, Gerritus et al 15 found that pioglitazone was associated with 22% relative risk reduction of MI (HR, 0.78, 95% CI, 0.63 to 0.96) compared with rosiglitazone after adjusting for baseline covariates. In both the Gerritus study and current analysis, baseline demographics/comorbidities were similar between groups that included results on all patients (including Ͻ65 years of age), and both studies included relevant covariates in their multivariate analyses; however, the current study used propensity score matching to ensure similarity at baseline between groups.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are similar to a recent retrospective study by Habib et al, 29 which found no difference in AMI between TZDs; however, they contrast another retrospective analysis of a younger, healthier insured population receiving rosiglitazone or pioglitazone by Gerritus et al 15 In review of administrative claims from US health plans, Gerritus et al 15 found that pioglitazone was associated with 22% relative risk reduction of MI (HR, 0.78, 95% CI, 0.63 to 0.96) compared with rosiglitazone after adjusting for baseline covariates. In both the Gerritus study and current analysis, baseline demographics/comorbidities were similar between groups that included results on all patients (including Ͻ65 years of age), and both studies included relevant covariates in their multivariate analyses; however, the current study used propensity score matching to ensure similarity at baseline between groups.…”
Section: Discussionsupporting
confidence: 83%
“…44 Subsequent large clinical trials, meta-analyses, and analyses of large insurance company databases have continued to provide similarly conflicting results with respect to increased risk of cardiovascular events. 45,46 Uncertainty remains as to whether rosiglitazone increases cardiovascular risks, but it is also clear that this drug does not substantially reduce these risks, a benefit that would be highly desirable in antidiabetic therapy.…”
Section: Adverse Effects Of Glitazonesmentioning
confidence: 99%
“…These models make the assumption that treatment changes are independent of cardiovascular outcomes and may lead to biased results in the presence of patient characteristics that vary over time, affecting both diabetes treatment choice and cardiovascular risk [79], a likely scenario in the context of a chronic disease requiring therapy adjustments commensurate to its natural progression. Few studies have accounted for time-dependent confounders [21,69]. Suitable strategies exist to address time-dependent confounding such as marginal structural models [80,81] or g computation [82].…”
Section: Temporality Considerations In Administrative Databasesmentioning
confidence: 99%
“…This approach is highly dependent on background knowledge and the specific research hypothesis, so it must be cautiously applied and carefully tailored to a particular study. A limited number of reviewed studies have considered lag periods in their study design [12,69]. The use of a lag period reduces the chances of protopathic bias (sometimes termed reverse causation), which may occur when conditions with some preclinical phase, e.g.…”
Section: Temporality Considerations In Administrative Databasesmentioning
confidence: 99%